A bionic inertial piezoelectric actuator with improved frequency bandwidth. (July 2021) - Xu, Zhi; Yang, Zhixin; Wang, Kuifeng; Li, Xuan; Liu, Yanwei; Dong, Jingshi; Huang, Hu
Highlights: An inertial piezoelectric actuator was developed by imitating the movement of frog during swimming. Various methods were employed to comparatively analyze the hexagonal compliant parallel mechanism. Frequency bandwidth of the actuator was significantly improved. The proposed actuator showed good comprehensive performances. Abstract: With features of simple structure and control, the inertial piezoelectric actuator is a promising type to achieve large working stroke and high positioning resolution. However, most of previously developed inertial piezoelectric actuators face the problems of low frequency bandwidth, motion speed, resolution as well as loading capacity, and thus require further improvement in comprehensive performances. For this purpose, inspired by the movement mode of frog's hind legs during swimming, a bionic inertial piezoelectric actuator was proposed in this study. The bionic motion principle and structure analysis of the designed inertial actuator were discussed in detail, followed by testing its output performances. The experimental results showed that the frequency bandwidth of the designed inertial actuator had been significantly increased to be 275 Hz, and correspondingly, the maximum motion speed reached 1.218 mm/s. In addition, the positioning resolution was 0.217 µm and the maximum horizontal load and vertical load were 0.6 N and 17 N, respectively. Comparative analysis indicated that compared to many previously reported inertial actuators, the comprehensive performances of the proposed actuator were significantly improved, being beneficial to its practical applications.